Influence of wettability characteristic on biofouling resistance of polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF) film embedded on glass fiber - Abdul Kadir, Muhammad Hazim; Hashim, Mohd Akmal; Jumahat, Aidah; Mohd Zahib, Zaidahtulakmal; Hashim, Ummu Raihanah; Mohd Fauzi, Mohd Afiq (Faculty of Applied Sciences, 2025)
Biofouling is a persistent issue for marine structures, reducing operational efficiency and increasing maintenance costs. Antifouling coatings prevent the accumulation of fouling organisms by forming physical barriers that inhibit the attachment of microorganisms, contaminants, and particles. However, conventional coatings often face limitations such as environmental degradation, frequent reapplication, and limited durability. This study examines the role of surface wettability in biofouling resistance by comparing polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF) films embedded with glass fiber (GF) to uncoated GF as a reference system, focusing on the influence of hydrophobic and hydrophilic properties. Contact angle measurements revealed distinct wettability characteristics: PTFE/GF exhibited high hydrophobicity (125.95°), while PVDF/GF (59.4°) and GF (63.1°) were hydrophilic. After 120 days of seawater exposure, PTFE/GF displayed the lowest biofouling growth (35.6%), significantly outperforming PVDF/GF (89.6%) and GF (94.7%). PTFE/GF also demonstrated self-cleaning capabilities, with fouling levels decreasing from 57.8% at 60 days to 35.6% at 120 days, emphasizing its durability and efficiency in harsh marine environments. The superior antifouling performance of PTFE/GF is attributed to its hydrophobicity, low surface energy, and the "lotus effect," which repels water and prevents microbial adhesion by allowing water droplets to bead and roll off, carrying away debris. In contrast, the hydrophilic PVDF/GF promotes water spreading, encouraging microbial attachment and biofilm formation, resulting in greater fouling growth. This study highlights the critical role of hydrophobicity in antifouling coatings, demonstrating that materials like PTFE significantly enhance biofouling resistance. These findings provide a foundation for developing durable, efficient antifouling solutions tailored to the challenging conditions of marine environments.